Preparation and evaluation of bioactive bilayer composite membrane PHB/β‐TCP with ciprofloxacin and vitamin D3 delivery for regenerative damaged tissue in periodontal disease. Issue 3 (11th August 2021) - Tayebi, Maryam; Parham, Shokoh; Abbastabbar Ahangar, Hossein; Zargar Kharazi, Anousheh
Abstract: Periodontal tissue engineering has made a tremendous change in the treatment of periodontal disease. In this study, electrophoresed poly‐hydroxy‐butyrate (PHB) scaffold, beta‐three calcium phosphate (β‐TCP) nano powder in 3, 5 and 7% wt, ciprofloxacin antibiotics, and vitamin D3 as the major materials along with electrospinning method are selected for remaking the scaffold. The fibers are smooth and beads‐free and have a good diameter (around 700 nm) and porosity (above 80%) indicates ideal conditions for the treatment of damaged tissue. The membrane with 5% ceramic has been selected as ideal membrane. The mention membrane has suitable mechanical properties. Studies have shown that adding ciprofloxacin to the membrane increases the rate of hydrophilicity. The addition of β‐TCP nano powder increased the bioactivity of this membrane. In terms of the drug release of ciprofloxacin and vitamin D3, 45% and 60% of drugs released within the first 24 h which in turn it shows the ability of the drugs controlled deliveration by the membrane. Accordingly, it could be concluded that this bilayer composite membrane with high bioactivity, high hydrophilicity, suitable mechanical properties, suitable morphology, and appropriate porosity has the ideal conditions for increased bone growth as well as proliferation and treatment the periodontal disease. Abstract :